The perspective of Net Promoter Score (NPS) in Grameenphone Ltd. - Rahman, Md. Ashikur (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2016.